Uso de levedura selecionada em escala piloto para a produção de cachaça de alambique - Gonçalves, Cleber Miranda (2015)
Cachaça corresponds to a beverage with characteristic flavor and aroma, constituted mainly of alcohol and water plus some other components formed in small amounts during the process of fermentation, distillation and aging, and known as the secondary products of alcoholic fermentation. The yeasts and fermentation conditions are considered to be the factors that influence the flavor of alcoholic beverages, since the majority of the secondary compounds responsible for the chemical and sensory quality of the beverage are formed during fermentation. The use of selected yeasts for the production of cane spirit has been studied, with a view to increasing productivity, gaining technological advantages and improving the sensory characteristics of the beverage. This study aimed to produce cachaça in pilot and alembic scales and evaluate the chemical composition of the beverages produced by selected strains of S. cerevisiae; verify the presence of the selected yeast at the end of the fermentation process on a pilot scale and carry out the evaluation of fermentation parameters of the selected strain in relation to commercial and wild inoculums. The following 16 strains of Saccharomyces cerevisiae were tested: SC52, SC60, SC82, SC91, SC102, SC114, SC129, SC138, SC174, SC177, SC179, SC184, SC219, SC220, SC225 and SC229. Among these, only the SC82 strain could pursue multiplication and fermentation scheme steps to produce cachaça in pilot and alembic scales. By RFLP mtDNA technique was possible to verify the permanence and dominance of selected yeast (SC82) at the end of fermentation process done in pilot scale. In the evaluation of fermentation parameters to S. cerevisiae strain SC82 had a shorter fermentation time (14h average) and a higher yield (48%), greater efficiency (93.94%) and a higher productivity (2.35 g/Lh) at the end of the third fermentation carried out in relation to commercial and wild inoculums. Regarding the results of the chemical analysis of cachaça produced in pilot and still scale, only the higher alcohol levels were above that allowed by Brazilian legislation in both produced beverages.